Doctor Who : the eleventh Doctor. Vol 1, After life - Ewing, Al, 1977- (Titan Comics, 2015)
"With a force of personality capable of bending time itself and all the energy of a star's exploding heart, the Doctor blasts into the hollow, tragic life of a woman with so much to offer--and gives her the chance to scream "Geronimo!" at the thrills, colors, and terrors of an infinite universe!"--Back cover.